Comparing the incidence of adverse events following topical versus oral non-steroidal anti-inflammatory drugs for knee osteoarthritis: a systematic review and meta-analysis - Alsharif, Maryam S.; Alharbi, Fouad S.; Alharbi, Ahmed M.; Alsaedi, Bassam S.; Alharbi, Nada S.; Alsharif, Mohammed S.; Alharbi, Shrooq S. (International Journal Of Community Medicine And Public Health, 2024)
Knee osteoarthritis is a prevalent condition that significantly impairs the quality of life, often managed with non-steroidal anti-inflammatory drugs (NSAIDs). While oral NSAIDs are widely used for their systemic effects, they are associated with a higher risk of adverse events (AEs). Topical NSAIDs offer localized approach with potentially fewer systemic side effects, making them an alternative. This meta-analysis compared the incidence of overall AEs associated with topical versus oral NSAIDs in patients with knee osteoarthritis. A systematic search was conducted in PubMed, Cochrane Library, and Embase for studies comparing AEs in patients with knee osteoarthritis treated with topical versus oral NSAIDs. Eight studies with a total of 2,181 participants were included. The pooled odds ratio (OR) for overall AEs was calculated, and heterogeneity among studies was assessed using I² statistic. Publication bias was evaluated using a funnel plot. The meta-analysis demonstrated that topical NSAIDs were associated with lower incidence of AEs compared to oral NSAIDs, with a pooled OR of 0.62 (95% CI: 0.38 to 1.00). This suggests that patients treated with topical NSAIDs were 38% less likely to experience AEs than those treated with oral NSAIDs (p=0.05). Significant heterogeneity was observed among the studies (I²=80%). The funnel plot indicated potential publication bias. Topical NSAIDs offer safer alternative to oral NSAIDs for managing knee osteoarthritis, particularly in reducing the risk of AEs. While the findings are promising, the high degree of heterogeneity and potential publication bias underscore the need for further research to confirm these results.